Plot of the indigenous law and andean cultural representativeness: sibillini discourses and forms of governance - Arroyo Aguilar, Sabino (2018)
From the anthropological perspective, the problem of the Indian, the indigenous race or the peasant question, are environments themselves to the historical process of the agrarian question of the nation-State, evidenced by a mode of prestige, power and conflict that settled in forms and relations of property, condition that extends to the present in the dichotomous image of the «modern Republic» and the «Andean communities».